The Validity of Sale and Purchase Contracts in the Al-Mujtama' Islamic Boarding School, Pamekasan: A Study Based on Imam al-Shafi'i's Al-Umm - Aisatul Qomariyah; Samheri (CV Edujavare Publishing, 2026)
Self-service transactions, in which buyers independently select goods, make payments, and collect change without the seller's direct involvement, represent an emerging form of commercial practice that has been increasingly adopted in various educational institutions, including Islamic boarding schools (pesantren). One such practice is implemented in the canteen of Al-Mujtama' Islamic Boarding School, Pamekasan, where transactions are conducted without verbal ijab (offer) and qabul (acceptance). This practice raises legal questions because, according to Imam al-Shafi'i, the ṣīghah (contractual expression) constitutes a fundamental element in the formation of a valid sale and purchase contract. This study aims to examine the validity of sale and purchase contracts implemented in the canteen of Al-Mujtama' Islamic Boarding School, Pamekasan, from the perspective of Imam al-Shafi'i as articulated in Al-Umm. The research employs a qualitative method using both empirical juridical and normative approaches. Primary data were collected through observations and interviews with the canteen management and students, while secondary data were obtained from Al-Umm, the Qur'an, Hadith, and relevant literature on Islamic economic law. Data were analyzed descriptively by comparing the transaction practices observed in the field with Imam al-Shafi'i's legal conception of contractual formation. The findings reveal that the transactions are conducted on the basis of mutual trust, voluntary consent, and established customary practice. Although no verbal ijab and qabul are expressed, the transactions satisfy the essential substantive requirements of mutual consent, certainty of the subject matter, price transparency, and the absence of gharar (excessive uncertainty) and fraudulent elements. Accordingly, based on an analysis of the concepts of contract formation, mu'āṭāh (sale by mutual conduct), 'urf (custom), and maqāṣid al-sharī'ah (the higher objectives of Islamic law), the practice may be regarded as substantively valid and demonstrates the flexibility of Islamic law in accommodating contemporary commercial practices while preserving fundamental Sharī'ah principles.